(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
The purpose of this paper is to present a Palaeohispanic inscription painted on ware dish found in Cártama (Málaga). It is an exceptional piece due to its place of discovery, where no Paleohispanic inscriptions are known so far. The graphic system in which it is written, its reading and the interpretation of its text are analyzed.